1980
DOI: 10.1136/pgmj.56.659.629
|View full text |Cite
|
Sign up to set email alerts
|

Clinical distinction of cerebral haemorrhage and cerebral infarction

Abstract: The clinical features of 62 cases of computerized axial tomography scan-proved cerebral haemorrhage and 81 cases of cerebral infarction in the carotid territory have been compared in a retrospective case note survey. The clinical features which can help in making the distinction between haemorrhage and infarction at the bedside are discussed and compared with those of classical teaching which referred only to post-mortem proved cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

1984
1984
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 6 publications
1
14
1
Order By: Relevance
“…In For the validation study it was evident (fig 4) that the accuracy of the diagnosis would be optimised when the cut off points were set at -1 and 1. The Siriraj stroke score was thus set at that level to differentiate between haemorrhage and infarction.…”
Section: Discussionmentioning
confidence: 99%
“…In For the validation study it was evident (fig 4) that the accuracy of the diagnosis would be optimised when the cut off points were set at -1 and 1. The Siriraj stroke score was thus set at that level to differentiate between haemorrhage and infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of patients with acute stroke in whom the diagnosis was made in life have largely confirmed the old observations that there are clinical features which are more common in one type of stroke than another (Harrison 1980, Allen 1983 (von Arbin et al 1981, Allen 1983). However, since about 80% of all patients have infarctions, the overall predictive accuracy of clinical diagnosis can be as high as 90%.…”
Section: Radiological Differential Diagnosismentioning
confidence: 77%
“…It has been reported that 59-80% of patients with haemorrhage have blood or xanthochromia in their CSF (Krabbe & Jorgenson 1931, Aring & Merritt 1935, Weisberg 1979, Harrison 1980, Britton et al 1983. Therefore the CSF examination as a test for haemorrhage may be specific (about 95%, Britton et al 1983) but has a false-negative rate of 20-40%.…”
Section: Radiological Differential Diagnosismentioning
confidence: 99%
“…This is slightly higher than the study by Harrison et al, where maximum cases were between 50-59 years (33.33%). 11 In a review of stroke epidemiology by Feigin; they concluded that the average age of patients affected by stroke is 70 years in men and 75 years in women. Our statistics show a similar age reflection.…”
Section: Age and Sexmentioning
confidence: 99%